2017
DOI: 10.1542/peds.2017-0183
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Methicillin-Resistant Staphylococcus aureus Bacteremia in Children

Abstract: Hospitalized children with MRSA bacteremia frequently suffered treatment failure and complications, but mortality was low. The odds of bacteremia-related complications increased with each additional day of bacteremia, emphasizing the importance of achieving rapid sterilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 28 publications
2
49
1
1
Order By: Relevance
“…It is worth acknowledging, however, that other investigators examining this issue have not found a consistent relationship between vancomycin MIC and clinical outcome in invasive staphylococcal infection (31,32). Such discrepancies in the literature might be a consequence of variability in MIC methodologies (33), definitions of primary outcomes, and/or global variability in strain types or intrinsic virulence.…”
Section: Discussionmentioning
confidence: 94%
“…It is worth acknowledging, however, that other investigators examining this issue have not found a consistent relationship between vancomycin MIC and clinical outcome in invasive staphylococcal infection (31,32). Such discrepancies in the literature might be a consequence of variability in MIC methodologies (33), definitions of primary outcomes, and/or global variability in strain types or intrinsic virulence.…”
Section: Discussionmentioning
confidence: 94%
“…Staphylococcus aureus (S. aureus) causes a substantial number of pediatric infections each year in the United States, with potential for severe complications including death. [1][2][3][4] Although the emergence of methicillin-resistant S. aureus (MRSA) led to a rapid increase in the number of S. aureus infections in children, 5 recent data suggest that S. aureus infections are declining in adults, driven primarily by decreases in MRSA. 6,7 Similar findings have been reported in pediatric populations, but these studies were limited to single centers and unique populations, such as military members or infants.…”
mentioning
confidence: 99%
“…There is increasing political and community concern because multiple approaches have failed or struggled to control the spread of HCAIs, resulting in high morbidity and mortality due to AMR infections developed during hospital stays. [150][151][152][153][154][155] Strategies aimed at minimizing and controlling HCAIs comprise active surveillance cultures (ASCs), contact isolation of patients colonized with epidemiologically significant pathogens, and pre-emptive isolation of high-risk patients. 156 It has been suggested that ASCs of all or certain highrisk patients and placing them under contact precautions will help to curb or eliminate the multidrug-resistant organisms (MDROs) that can trigger HCAIs.…”
Section: Screening and Cohorting Patientsmentioning
confidence: 99%